The Role of Community Counselors (PK) Towards Children's Clients in Bapas Class I Pekanbaru - Gustaf, Ghifari Ahmad; Tutrianto, Rio (Teunuleh Publisher, 2025)
The Pekanbaru Class I Correctional Center (Bapas) plays an important role in supporting the juvenile criminal justice system, especially in providing guidance, assistance, and supervision to Children Facing the Law (ABH). This study aims to comprehensively examine the role of Community Counselors (PK) in carrying out their functions to children's clients, as well as identify various obstacles that arise in its implementation. This study uses a descriptive qualitative method, with data collection techniques through in-depth interviews and documentation. Data analysis was conducted based on Travis Hirschi's social control theory which includes four main elements: attachment, commitment, involvement, and belief. The findings show that the role of PK is not only limited to administrative and legal aspects through the preparation of Litmas and assistance in the judicial process, but also includes social-emotional functions by building closeness and moral support for child clients. The four elements of Hirschi's theory are strongly seen in the relationship formed between PK and the child's client, which also supports the process of rehabilitation and reintegration into society. However, the implementation of the role of PK in the field still faces various obstacles, including the limited number and competence of human resources, lack of family support, and the stigma from the surrounding environment towards fostered children. For this reason, it is necessary to strengthen institutions, increase professional capacity through continuous training, and synergy between agencies to create a more inclusive, effective, and sustainable child development system.